Effects of Substitution of Alfalfa Meal with Dried Tomato Pomace (DTP) in Newzealand Male Rabbits Rations on Semen Characteristics and Some Blood Constituents - Elkomy, Alaa E.; Zahran, S.A.; El-Azab, A.I.; El-Azab, M.A. (Pakistan Journal of Nutrition, 2016)
This study aimed to investigate the effect of incorporation of dried tomato pomace (DTP) into rabbit bucks rations on semen quality characteristics, libido and some seminal plasma and blood biochemical constituent. A total of twenty New Zealand White male rabbits, 8 months old, were randomly divided into four equal groups (5 bucks for each). Group one served as a control group, which received a basal diet, while, groups 2, 3 and 4 received a diet containing 10, 15 and 20% of DTP for 12 weeks as an experimental period, respectively. There was no effect due to feed rabbit bucks on DTP inclusion diets on live body weight, while, feed consumption was decreased by 9.3, 11.2 and 14.8% for 10, 15 and 20% TP levels, but this decrease was non-significant. Results indicated that 10 or 15% DTP groups showed significant improvement in semen ejaculate volume, sperm cell concentration, sperm motility, total sperm out-put, total motile sperm and total motile normal sperm and the rate of sperm abnormalities was decreased. On the other hand, 20% DTP has positive effect on semen measurements compared to the control however, this improvement was non-significant. Seminal plasma total proteins and albumin appeared remarkably higher for bucks’ fed DTP at any studied level especially for 20% DTP than the control group, whereas, calcium concentration was markedly decreased in all DTP groups. Blood hematological parameters (Hb, PCV, RBC and WBC) were increased significantly in DTP feeding groups compared to the control and these finding were more prominent for the bucks put on 10% DTP level. Liver enzymes activities (AST and ALT) were significantly decreased due to added DTP in male rabbits’ diets with any level compared to the control group. Testicular parenchyma of 10 and 15% DTP groups showed a better histological characterization with healthy somniferous tubules (ST) compared to the control or the 20% DTP level and 20% group still showed histological characterization better than the control group. It could be concluded that addition of DTP in the mature male rabbit’s diets by 10, 15 and 20% levels has positive effect on the semen quantity and quality, as well as, some blood biochemical properties of the white New Zealand breed.